The E and B EXperiment: A balloon-borne cosmic microwave background anisotropy probe ... - Hillbrand, Seth Nathaniel (Columbia University, 2014)
The E and B Experiment (EBEX), is a balloon-borne sub-orbital cosmic microwave background polarimeter, designed to measure polarization levels in the microwave spectrum. EBEX recently completed an 11-day Antarctic long duration balloon (LDB) science flight in January, 2013. ~1000 transition edge sensor bolometric detectors in three frequency bands centered at 150, 250 and 410 GHz sampled a large segment of the southern sky. Over 1.5TB of data were collected during the LDB flight. In this thesis, we describe the design and performance of the EBEX software components monitoring and controlling the system during the flight, including automation, telemetry, data storage and readout array management. We also describe the design and development of a novel attitude reconstruction system for a balloon-borne pointed observation platform based on a daytime star camera and 3-axis gyroscopes. The data gathered during the LDB flight are analyzed and the results presented showing attitude reconstruction error at less than ...